Exploring the relationships between dominance behavioral system, mentalization, theory of mind and assertiveness: analysis in a non-clinical sample - Cerciello, Francesco; Esposito, Clara; La Penna, Ilaria; Sica, Luigia Simona; Frolli, Alessandro (Frontiers in Psychology, 2024)
Introduction. The dominance behavioral system, a fundamental aspect of human behavior, orchestrates the drive for dominance, regulates dominant-subordinate dynamics, and shapes responses to perceived power dynamics. While the existing literature extensively delves into the components of this system, scant attention is paid to its interplay with mentalization, theory of mind, and assertiveness. Moreover, gender disparities in dominance behaviors are largely studied in terms of biological variables (levels of testosterone) and clinical populations. This study aims to understand the relationships between activation strategies of the dominance behavioral system, mentalization processes, theory of mind abilities, and levels of social discomfort in assertive communication. Moreover, to identify gender differences in the dominance behavioral system in a non-clinical sample. Methods. Our sample was composed of 67 students from a non-clinical population. They claimed the absence of any psychological, neurological, or developmental disorders. Results. A regression analysis was performed, and we found that levels of mentalization predict levels of hyperactivation of dominance behavioral system, but no significant results for the deactivation levels of the system were found. Moreover, no gender differences were found in levels of activations of the dominance behavioral system. Conclusion. These findings underscore the pivotal role of mentalization abilities in interpersonal dynamics, emphasizing the need for individuals to navigate social interactions adeptly. Furthermore, our research unveils implications for individual well-being and psychopathology, urging further investigation into how these dimensions intersect with various psychological disorders. By discerning the intricate mechanisms at play, we can develop targeted therapeutic interventions tailored to specific behavioral patterns, ultimately enhancing psychological resilience and fostering healthier social relationships in a non-clinical population.